Modified doped lithium phosphorus sulfur chlorine solid electrolyte as well as preparation method and application thereof
The sulfur-silver germanium ore structure formed by double doping of Al and Cl, modified doped lithium phosphorus thiochlorine solid electrolyte solves the ionic conductivity and stability of the Li6PS5Cl system electrolyte, and achieves higher ionic conductivity and stability.
Patent Information
- Application Number
- CN202411857321.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The Li6PS5Cl system electrolyte has limited ionic conductivity and intrinsic interface instability, making it difficult to meet the high stability and high energy density requirements of all-solid-state lithium batteries.
The sulfur-silver germanium ore structure formed by double doping of Al and Cl is modified to dopant lithium phosphorus thiochlorine solid electrolyte to improve the ion mixing ratio and the expansion of ion channels within its crystal lattice.
The ionic conductivity and stability of the Li6PS5Cl system electrolyte is significantly improved, with an ionic conductivity exceeding 3mS/cm, enhancing the stability to lithium.
Smart Images

Figure CN119674199A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a modified doped lithium phosphorus sulfur chlorine solid electrolyte and a preparation method and application thereof. Background Art
[0002] Solid-state batteries refer to lithium-ion batteries that use solid electrolytes instead of organic liquid electrolytes. They have higher safety and higher energy density. As a key component of all-solid-state batteries, solid electrolytes have always been the focus of extensive research, especially sulfide solid electrolytes, oxide solid electrolytes, and polymer solid electrolytes.
[0003] Sulfide electrolytes are considered to be the most promising candidates due to their high ionic conductivity and suitable mechanical properties. 10 GeP2S 12 and Li6PS5Cl (lithium phosphorus sulfur chloride), the room temperature ionic conductivity of both can reach 10 -2 and 10 -3 S / cm. Although the ionic conductivity of Li6PS5Cl is higher than that of Li 10 GeP2S 12 Although the cost is lower than that of solid-state lithium batteries, it has greater potential in practical applications.
[0004] However, as a research hotspot among all argyrodite-type sulfide solid electrolytes, Li6PS5Cl still faces some challenges, such as limited ionic conductivity and intrinsic interface instability. Therefore, it is of great significance to develop Li6PS5Cl system electrolytes with high stability and high ionic conductivity. Summary of the invention
[0005] The object of the present invention is to provide a modified doped lithium phosphorus sulfur chlorine solid electrolyte and a preparation method and application thereof, which can improve the ionic conductivity and stability of the Li6PS5Cl system electrolyte.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a modified doped lithium phosphorus sulfur chlorine solid electrolyte, the chemical formula of which is Li 6-5x Al x P 1-x S 5- 5x Cl 1+3x , where 0<x≤0.5.
[0008] Preferably, x=0.1-0.2.
[0009] The present invention provides a method for preparing the modified doped lithium phosphorus sulfur chlorine solid electrolyte described in the above technical solution, comprising the following steps:
[0010] In an argon atmosphere, lithium sulfide, phosphorus pentasulfide, lithium chloride and a modified dopant are mixed to obtain a mixed material;
[0011] After the mixed material is sealed, ball milling is performed to obtain a precursor powder;
[0012] The precursor powder is sequentially cold-pressed into tablets and sintered to obtain a modified doped lithium phosphorus sulfur chlorine solid electrolyte;
[0013] The modified dopant includes LiAlCl4 or a mixture of AlCl3 and LiCl.
[0014] Preferably, the molar ratio of lithium sulfide, phosphorus pentasulfide and lithium chloride is 5:1:2.
[0015] Preferably, the molar ratio of the modified dopant to phosphorus pentasulfide is 2x:(1-x), 0<x≤0.5.
[0016] Preferably, the ball milling speed is 350-550 rpm, the time is 4-20 hours, and the ball-to-material ratio is 10-60:1.
[0017] Preferably, the cold-pressed tablet is formed at a pressure of 250 to 360 MPa, and the pressure holding time is 1 to 5 min.
[0018] Preferably, the sintering temperature is 450° C. to 550° C., the time is 4 to 16 hours, and the heating rate to the sintering temperature is 1 to 5° C. / min.
[0019] Preferably, the particle size of the modified doped lithium phosphorus sulfur chlorine solid electrolyte is 2 to 20 μm.
[0020] The present invention provides the use of the modified doped lithium phosphorus sulfur chlorine solid electrolyte described in the above technical solution or the modified doped lithium phosphorus sulfur chlorine solid electrolyte prepared by the preparation method described in the above technical solution in an all-solid-state battery.
[0021] The present invention provides a modified doped lithium phosphorus sulfur chlorine solid electrolyte, which is a sulfide solid electrolyte with a argyrodite structure formed by dual doping of Al and Cl. The dual doping method can increase the ion mixing ratio inside the lattice of Li6PS5Cl and expand the ion channel. Specifically, the larger size of the metal cation Al 3+ Partial substitution of the P site can broaden the Li + Migration channel, reducing Li + Migration barrier; Cl - Partially replace the S position and increase the Cl in the structure - / S2- Anionic disorder, thus inducing Li + Density delocalization and Li + The ionic conductivity of the Li6PS5Cl system electrolyte and its stability to lithium are improved. The ionic conductivity of the modified doped lithium phosphorus sulfur chlorine solid electrolyte prepared by the present invention is greater than 3mS / cm.
[0022] The modified doped lithium phosphorus sulfur chlorine solid electrolyte provided by the present invention has an appearance of grayish white powder, is uniform and free of foreign matter, is of argyrodite type, has a space group of F43m in the crystal structure, and has a particle size of 2 to 20 μm.
[0023] The preparation method of the modified doped lithium phosphorus sulfur chlorine solid electrolyte of the present invention is simple, and the precursor powder can be obtained by ball milling for only 8 hours, and no scattered precious metals are used, thereby reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD diagrams of the solid electrolyte materials prepared in Examples 1 to 5 and Comparative Example 1;
[0025] Figure 2 This is a SEM image of the solid electrolyte material prepared in Example 1. DETAILED DESCRIPTION
[0026] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0027] The present invention provides a modified doped lithium phosphorus sulfur chlorine solid electrolyte, the chemical formula of which is Li 6-5x Al x P 1-x S 5- 5x Cl 1+3x , where 0<x≤0.5.
[0028] In the present invention, x is more preferably 0.1 to 0.2, and more preferably 0.15 to 0.2.
[0029] The present invention provides a method for preparing the modified doped lithium phosphorus sulfur chlorine solid electrolyte described in the above technical solution, comprising the following steps:
[0030] In an argon atmosphere, lithium sulfide, phosphorus pentasulfide, lithium chloride and a modified dopant are mixed to obtain a mixed material;
[0031] After the mixed material is sealed, ball milling is performed to obtain a precursor powder;
[0032] The precursor powder is sequentially cold-pressed into tablets and sintered to obtain a modified doped lithium phosphorus sulfur chlorine solid electrolyte;
[0033] The modified dopant includes LiAlCl4 or a mixture of AlCl3 and LiCl.
[0034] In the present invention, the molar ratio of lithium sulfide, phosphorus pentasulfide and lithium chloride is preferably 5:1:2.
[0035] In the present invention, the modified dopant includes LiAlCl4 or a mixture of AlCl3 and LiCl; the molar ratio of AlCl3 to LiCl in the mixture of AlCl3 and LiCl is preferably 1:1.
[0036] In the present invention, the molar ratio of the modified dopant to phosphorus pentasulfide is 2x:(1-x), 0<x≤0.5.
[0037] The present invention preferably mixes lithium sulfide, phosphorus pentasulfide, lithium chloride and a modified dopant, transfers the obtained mixture to a crusher for crushing, mixes evenly, and transfers the obtained mixed powder to an agate ball mill for ball milling. During the process, the powder needs to be crushed and ground after agglomeration to complete the transformation of the powder from a crystalline state to an amorphous state.
[0038] The process of preparing the modified doped lithium phosphorus sulfur chlorine solid electrolyte of the present invention is preferably carried out in an inert gas atmosphere; the inert gas is preferably argon.
[0039] In the present invention, the rotation speed of the ball mill is preferably 350-550 rpm, more preferably 400-500 rpm, the time is preferably 4-20 h, more preferably 8 h, and the ball-to-material ratio (i.e., the ratio of the material in the ball mill to the grinding body mass) is preferably 10-60:1, more preferably 30:1.
[0040] In the present invention, the pressure of the cold-pressed tablet is preferably 250-360 MPa, more preferably 300-360 MPa, and the holding time is preferably 1-5 min, more preferably 3 min. The present invention has no special limitation on the tableting mold used for the cold-pressed tablet, and any corresponding mold known in the art can be used.
[0041] After the cold-pressed tablets are completed, the present invention preferably transfers the obtained product to a corundum crucible, sintering it in a box-type atmosphere furnace, and naturally cooling it to room temperature to obtain a modified doped lithium phosphorus sulfur chlorine solid electrolyte.
[0042] In the present invention, the sintering temperature is preferably 450°C to 550°C, more preferably 500°C, the time is preferably 4 to 16 hours, more preferably 8 to 12 hours, and the heating rate to the sintering temperature is preferably 1 to 5°C / min, more preferably 2 to 3°C / min.
[0043] In the present invention, the particle size of the modified doped lithium phosphorus sulfur chlorine solid electrolyte is preferably 2 to 20 μm, and the appearance is off-white powder.
[0044] The present invention provides the use of the modified doped lithium phosphorus sulfur chlorine solid electrolyte described in the above technical solution or the modified doped lithium phosphorus sulfur chlorine solid electrolyte prepared by the preparation method described in the above technical solution in an all-solid-state battery. The present invention has no special limitation on the method of the application, and the application can be carried out according to methods well known in the art.
[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] Example 1
[0047] Li 5.25 Al 0.15 P 0.85 S 4.25 Cl 1.45 (x=0.15) Preparation of solid electrolyte:
[0048] According to the molar ratio of Li2S: P2S5: LiCl: LiAlCl4 = 2.125: 0.425: 0.85: 0.15, 9.76g Li2S, 9.45g P2S5, 3.60g LiCl and 2.64g LiAlCl4 were weighed, the above raw materials were poured into a pulverizer and mixed, and then transferred to an agate lined ball mill, the ball material ratio was 30:1, the sealed ball mill was placed on the ball mill, the speed was 400rpm, the ball milling time was 8h, and a tablet pressing mold was used to apply a pressure of 360Mpa to the precursor powder obtained by ball milling, the pressure was maintained for 3min, and the cold pressed tablets were transferred to the obtained tablets in a closed crucible, 500℃ in an atmosphere furnace, the heating rate was 3℃ / min, sintered for 12h, and naturally cooled to room temperature to obtain a modified doped lithium phosphorus sulfur chlorine solid electrolyte. The above process was completed in a glove box.
[0049] Example 2
[0050] Li 5.5 Al 0.1 P 0.9 S 4.5 Cl 1.3 (x=0.1) Preparation of solid electrolyte:
[0051] The preparation method provided in this embodiment is the same as that in Example 1, the only difference is that: the molar ratio of Li2S:P2S5:LiCl:LiAlCl4=2.25:0.45:0.9:0.1, 10.34g Li2S, 10.00g P2S5, 3.81g LiCl and 1.76g LiAlCl4 are weighed.
[0052] Example 3
[0053] Li5Al 0.2 P 0.8 S4Cl 1.6 (x=0.2) Preparation of solid electrolyte:
[0054] The preparation method provided in this embodiment is the same as that in Example 1, except that 9.19 g Li2S, 8.89 g P2S5, 3.39 g LiCl and 3.51 g LiAlCl4 are weighed according to the stoichiometric ratio of Li2S:P2S5:LiCl:LiAlCl4=2:0.4:0.8:0.2.
[0055] Example 4
[0056] Li 4.5 Al 0.3 P 0.7 S 3.5 Cl 1.9 (x=0.3) Preparation of solid electrolyte:
[0057] The preparation method provided in this embodiment is the same as that in Example 1, the only difference is that: at a molar ratio of Li2S:P2S5:LiCl:LiAlCl4=1.75:0.35:0.7:0.3, 8.04g Li2S, 7.78g P2S5, 2.97g LiCl and 5.27g LiAlCl4 are weighed.
[0058] Example 5
[0059] Li 5.25 Al 0.15 P 0.85 S 4.25 Cl 1.45 (x=0.15) Preparation of solid electrolyte:
[0060] The preparation method provided in this embodiment is the same as that in Example 1, except that the molar ratio of Li2S:P2S5:LiCl:AlCl3 and LiCl mixture is 2.125:0.425:0.85:0.15, and 9.76g Li2S, 9.45g P2S5, 3.60g LiCl and 2.64g AlCl3 and LiCl mixture are weighed (the molar ratio of AlCl3 to LiCl in the AlCl3 and LiCl mixture is 1:1).
[0061] Example 6
[0062] Li 5.25 Al 0.15 P 0.85 S4.25 Cl 1.45 (x=0.15) Preparation of solid electrolyte
[0063] According to the molar ratio of Li2S:P2S5:LiCl:LiAlCl4=2.125:0.425:0.85:0.15, 4.88g Li2S, 4.72g P2S5, 1.80g LiCl and 1.32g LiAlCl4 were weighed, the above raw materials were poured into a grinder and mixed, and then transferred to an agate lined ball mill, the ball-to-material ratio was 60:1, the sealed ball mill was placed on the ball mill, the speed was 450rpm, the ball milling time was 20h, and a tablet pressing mold was used to apply a pressure of 360Mpa to the precursor powder obtained by ball milling, the pressure was maintained for 5min, and the tablets were cold pressed. The obtained tablets were transferred to a closed crucible, sintered at 500℃ in an atmosphere furnace with a heating rate of 5℃ / min for 12h, and naturally cooled to room temperature to obtain a solid electrolyte.
[0064] The above processes were all completed in the glove box.
[0065] Example 7
[0066] Li 5.25 Al 0.15 P 0.85 S 4.25 Cl 1.45 (x=0.15) Preparation of solid electrolyte:
[0067] According to the molar ratio of Li2S: P2S5: LiCl: LiAlCl4 = 2.125: 0.425: 0.85: 0.15, 5.86g Li2S, 5.67g P2S5, 2.16g LiCl and 1.58g LiAlCl4 were weighed, the above raw materials were poured into a pulverizer and mixed, and then transferred to an agate lined ball mill, the ball-to-material ratio was 30:1, the sealed ball mill was placed on the ball mill, the speed was 500rpm, the ball milling time was 20h, and a tablet pressing mold was used to apply 360Mpa pressure to the precursor powder obtained by ball milling, the pressure was maintained for 5min, and the cold pressed tablets were transferred to the obtained tablets in a closed crucible, 450℃ in an atmosphere furnace, the heating rate was 2℃ / min, sintered for 12h, and naturally cooled to room temperature to obtain a solid electrolyte. The above process was completed in a glove box.
[0068] Comparative Example 1
[0069] Preparation of Li6PS5Cl solid electrolyte:
[0070] The preparation method provided in this comparative example is the same as that in Example 1, the only difference is that: at a molar ratio of Li2S:P2S5:LiCl=5:1:2, 11.49g Li2S, 11.11g P2S5 and 4.24g LiCl are weighed.
[0071] Characterization
[0072] X-ray powder diffraction of different solid electrolytes was performed using CuKα radiation. Figure 1 XRD diagrams of the solid electrolyte materials prepared in Examples 1 to 5 and Comparative Example 1; Figure 1 It is shown that the solid electrolytes prepared in Examples 1 to 5 and Comparative Example 1 have obvious diffraction peaks at 2θ=25.5±1.0°, 2θ=29.9±1.0° and 2θ=31.3±1.0°, indicating that the solid electrolyte is of argyrodite type, and the space group of the crystal structure is F43m.
[0073] Figure 2 is a SEM image of the solid electrolyte material obtained in Example 1, as shown Figure 2 As shown, the particle size of the material is 2 to 20 μm, and the particle distribution is relatively uniform, and there are no obvious hole defects on the particle surface.
[0074] Test Case
[0075] The solid electrolytes prepared in each embodiment and each comparative example were respectively subjected to ion conductivity tests and critical current density tests of lithium symmetric batteries (the larger the value, the better the stability).
[0076] The ionic conductivity was measured by electrochemical impedance spectroscopy (EIS). The Li-Li symmetric battery assembly process was carried out in a glove box, and the constant current charge and discharge test was carried out using a Wuhan Blue Electric charge and discharge tester.
[0077] The results are shown in Table 1.
[0078] Table 1 Performance data of solid electrolytes in Examples 1 to 7 and Comparative Example 1
[0079]
[0080]
[0081] It can be seen from Table 1 that when x=0.1~0.2 and the dopant is LiAlCl4, the ionic conductivity and critical current density of the corresponding modified solid electrolyte show better results than those of the unmodified Li6PS5Cl.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified doped lithium phosphorus sulfur chlorine solid electrolyte, characterized in that: The chemical formula is Li 6-5x Al x P 1-x S 5-5x Cl 1+3x , where 0<x≤0.
5.
2. The modified doped lithium phosphorus sulfur chlorine solid electrolyte according to claim 1, characterized in that: x=0.1~0.2。 3. The method for preparing the modified doped lithium phosphorus sulfur chlorine solid electrolyte according to claim 1 or 2, characterized in that: The following steps are involved: In an argon atmosphere, lithium sulfide, phosphorus pentasulfide, lithium chloride and a modified dopant are mixed to obtain a mixed material; After the mixed material is sealed, ball milling is performed to obtain a precursor powder; The precursor powder is sequentially cold-pressed into tablets and sintered to obtain a modified doped lithium phosphorus sulfur chlorine solid electrolyte; The modified dopant includes LiAlCl4 or a mixture of AlCl3 and LiCl.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the lithium sulfide, phosphorus pentasulfide and lithium chloride is 5:1:
2.
5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of the modified dopant to phosphorus pentasulfide is 2x:(1-x), 0<x≤0.
5.
6. The preparation method according to claim 5, characterized in that: The rotation speed of the ball mill is 350-550 rpm, the time is 4-20 hours, and the ball-to-material ratio is 10-60:
1.
7. The preparation method according to claim 6, characterized in that: The cold pressed tablet has a pressure of 250-360 MPa and a holding time of 1-5 min.
8. The preparation method according to claim 7, characterized in that: The sintering temperature is 450° C. to 550° C., the sintering time is 4 to 16 hours, and the heating rate to the sintering temperature is 1 to 5° C. / min.
9. The preparation method according to claim 8, characterized in that: The particle size of the modified doped lithium phosphorus sulfur chlorine solid electrolyte is 2 to 20 μm.
10. Use of the modified doped lithium phosphorus sulfur chlorine solid electrolyte according to claim 1 or 2 or the modified doped lithium phosphorus sulfur chlorine solid electrolyte prepared by the preparation method according to any one of claims 3 to 9 in an all-solid-state battery.
Citation Information
Patent Citations
Doped phosphorus-sulfur iodide solid electrolyte and preparation method and application thereof
CN111092262A
Lithium-containing argyrodite solid electrolyte with dopant and preparation method of lithium-containing argyrodite solid electrolyte
CN111430808A
Lithium argyrodite type solid electrolyte containing lithium halide in-situ precipitated phase as well as preparation method and application of lithium argyrodite type solid electrolyte
CN115051027A
Cited By
High-entropy all-solid-state electrolyte and preparation method and application thereof
CN121355360A
Lithium sulfide composition as well as preparation method and application thereof
CN121905945A
Preparation method of sulfide solid electrolyte
CN122091720A